FAKTOR-FAKTOR PENGAWASAN MESIN PARKIR OTOMATIS KOTA BANDUNG - Tati Sarihati (FISIP Universitas Langlangbuana, 2019)
Supervision is an important factor to minimize the occurrence of irregularities in the implementation of government organizational functions. One of the main objectives of the supervision carried out by the Integrated Service Unit (UPT) of the Department of Transportation of the City of Bandung is to increase regional income through parking fees for automatic parking machines. In practice, there are several obstacles that reduce the original income of the city of Bandung. In connection with these conditions, a study is needed to find out and analyze how Automatic Parking supervision by the Department of Transportation of the City of Bandung and what factors influence and the efforts made to overcome the obstacles encountered. This type of research is a descriptive study with a qualitative approach. Data collection techniques in this research were carried out through participant observation, in-depth interviews, and documentation studies. Determination of informants was done by using purposive sampling technique. The analysis used in this study is to implement measures of supervision consisting of direct supervision, indirect supervision and supervision based on exceptions. The results of the study explained that the supervision problem: